2005
DOI: 10.2460/javma.2005.226.1681
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of omeprazole paste for prevention of gastric ulcers in horses in race training

Abstract: Sham-dose-treated horses had significantly higher ulcer scores than did horses treated with any of the omeprazole dosages evaluated. Among horses treated with omeprazole, there was no significant interaction of dose (1 or 2 mg/kg) and loading dose; therefore, the lowest effective dose (1 mg/kg) was evaluated in the dose confirmation portion of the study. In the dose confirmation study, 4 of 39 (10%) sham-dose-treated horses remained ulcer free, which was significantly different from the proportion of horses (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 13 publications
2
20
0
5
Order By: Relevance
“…The efficacy of omeprazole in treatment and prevention of gastric ulcer has been reported in racehorses and foals [5,7,8,14]. Our study demonstrated the efficacy in prevention of occurrence of gastric ulcers for young thoroughbred horses during training.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…The efficacy of omeprazole in treatment and prevention of gastric ulcer has been reported in racehorses and foals [5,7,8,14]. Our study demonstrated the efficacy in prevention of occurrence of gastric ulcers for young thoroughbred horses during training.…”
supporting
confidence: 68%
“…Our study demonstrated the efficacy in prevention of occurrence of gastric ulcers for young thoroughbred horses during training. McClure et al reported the efficacy of omeprazole in prevention of gastric ulcers in racehorses [7]. Only 18.4% (7/38) of omeprazole treated horses developed gastric ulcers, while 89.7% (35/39) of sham-dosed horses developed gastric ulcers during their study [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estos resultados difieren de lo informado por Bezdeková y colaboradores (21) y McClure y colaboradores (22), quienes hallaron prevalencias que oscilan entre el 10 y el 40 % en la mucosa glandular y manifiestan que en esta región gástrica es menos frecuente su presentación debido a su sistema intrínseco de defensa. Sin embargo, la alta frecuencia en el presente estudio se debe posiblemente a la disminución de los factores defensivos de la mucosa glandular, ocasionados quizás por la administración de fármacos que bloquean la síntesis de prostaglandinas citoprotectoras como la E2 (23), estados de estrés que inhiben la síntesis de prostaglandinas endó-genas por el aumento en la liberación de corticosteroides, así como la disminución en el consumo de agua y alimentos, debido a que la secreción del ácido en el estómago del caballo es permanente.…”
Section: Resultsunclassified
“…Esto se puede atribuir a cambios provocados por estados de estrés, que inhiben la síntesis de prostaglandinas endógenas, o por el aumento en la liberación de corticosteroides y disminución del flujo sanguíneo de la mucosa gástrica, en lo cual puede haber vasoconstricción local con lesiones por isquemia; se incrementa la secreción de ácido clorhídrico y pepsina, lo que hace que se aumente la exposición de la mucosa a estos agentes (22,31).…”
Section: Resultsunclassified